Patients’ Comprehension of Mindfulness-Based Cognitive Behavioral Therapy in an Outpatient Clinic for Resistant Depression: A Cross-Sectional Study - Rodrigues, Michele F.; Campos, Carlos; Pelucio, Luisa; Barreto, Izabel; Machado, Sergio; Appolinario, Jose C.; Nardi, Antonio E.; Levitan, Michelle (Frontiers in Psychology, 2019)
The current study investigated the comprehension of mindfulness-based cognitive behavioral therapy (MBCT) by patients with resistant depression at the Psychiatry Institute of the Federal University of Rio de Janeiro, Brazil. This was the first time the model was used in the institution to treat these patients. In this brief study, 28 patients were invited to participate in a baseline session of MBCT, in which two trained therapists explained the model and conducted experimental exercises with them. At the end of the intervention, the patients completed a self-administered questionnaire to assess their understanding of the method’s goals. More than 75% of the patients rated the intervention as comprehensible and workable. Compared to patients with depression, patients with anxiety had a better understanding of the mindfulness framework (6.5%) and the meaning of cognitive behavioral therapy (17.6%). Patients that completed the intervention described the baseline session of MBCT as comprehensive and acceptable. The results of this “baseline session” will be compared with those of psychotherapy in a following study.